Development of ecotourism in Blubuk Village through sustainable environmental management - Aristya, Ganies Riza; Wulandari, Mutiara Tri; Dimas, Abimanyu; Sritanjung, Opi; Ramadhani, Gilang Afif Setya; Ishana, Aurelia Araya; Fadhlurrohman, Galih Dzaky; Azzahira, Faiha Azka; Muliawati, Adina; Sofyantoro, Fajar (Community Empowerment, 2025)
Blubuk Hamlet, Kulon Progo is a rural area with great potential in agriculture and ecotourism. However, the community faces challenges in maximizing this potential due to limited knowledge. This community service program aims to empower the local community through waste utilization to have economic value. The program uses various methods, including training, participatory mapping, and focus group discussions (FGDs). The main activities include maggot cultivation for fish feed production, biodiesel production from used cooking oil, eco-enzyme production from organic waste, and ecotourism planning. The results showed that 80% of training participants successfully understood maggot cultivation techniques, collectively produced 3 kg of maggots, and produced 1 kg of fish pellets in two months. Eco-enzyme production from household organic waste reduced waste by 40%, with 85% of participants using the product as a natural cleaner and fertilizer. Biodiesel production produced 2 liters of biodiesel from 5 liters of used cooking oil, which was tested and used as an alternative fuel. This program successfully introduced the concept of community-based ecotourism management and increased public understanding of the economic potential that can be developed from local natural resources.